Understanding the energy yield of photovoltaic modules in different climates by linear performance loss analysis of the module performance ratio. Issue 5 (20th March 2017) - Schweiger, Markus; Herrmann, Werner; Gerber, Andreas; Rau, Uwe
Abstract : The energy yield of 15 different photovoltaic module technologies is measured during one year of operation at four locations (Germany, Italy, India, Arizona) corresponding to four different climate zones. The data are analysed in terms of a linear performance loss analysis for the module performance ratio (MPR) taking into account the influence of module temperature, low irradiance conditions, spectral and angular effects and soiling. This analysis is based on an independent characterisation of the modules in the laboratory combined with site specific data accumulated during operation. The model predicts trends of the measured MPR due to different module technologies and different locations.